Merging Educational Finance Reform and Desegregation Goals - Kazal-Thresher, Deborah M. (Education Policy Analysis Archives, 1993)
Educational finance reforms and desegregation have both sought to address inequities in educational opportunities for minorities and low income families. The recent methods of addressing desegregation issues have tended to focus on attaining racial balance rather than educational quality, however. This paper explores how desegregation goals can be merged with educational finance reform to more systematically address educational quality in schools serving low income and minority populations. By moving toward centralized control over school financing, the inequity of school outcomes that are based on unequal school resources can be reduced. In addition, state determined expenditures when combined with desegregation monies, would meet the original intention of desegregation funds by clearly providing add-on monies for additional services for minority children, while at the same time, creating a better monitoring mechanism.